Bert W. O’Malley (1936–2025): A great scientist, mentor, and proud Irishman - Donald P. McDonnell (Proceedings of the National Academy of Sciences, 2026)
Bert W. O’Malley, the “father/grandfather” of the field of molecular endocrinology passed away on November 11, 2025, at the age of 88. In a distinguished career that spanned over 60 years, he probed fundamental aspects of steroid hormone action, work that informed our understanding of the biology of hormones and how their dysregulated activity underlies the pathobiology of reproductive abnormalities, metabolic diseases, and cancer. His work provided insights that have contributed considerably to the transition from empiric to mechanism-based discovery of drugs that can be used to manipulate steroid/nuclear hormone receptor action for therapeutic benefit. The field has lost a leader but the impact of his large body of work will endure.